THE INVESTIGATION OF IMPORTANCE AND PLACE IN TRAINING PIANO REPERTOIRE OF JOHN STANLEY’S VOLUNTARIES - İzzet YÜCETOKER (Fırat University, 2020)
John Stanley is one of the England baroque composers. Result of an accident at a young age to lose sight Stanley, musical education began at a young age and period has been one of the talented organists. Producing works in almost every type of this talented composer's best-known compositions are voluntary which was written for the organ. Voluntary was found by England baroque composers, usually is the name given to works written in two parts. Volunteri of Stanley, containing in perfect counterpoint, dulcet melodies, in a technical sense and which includes baroque art baroque style properties has a structure containing perfectly. However, as a result of the research works of John Stanley and has been found to be recognized in Turkey. This research studied piano in the baroque style of John Stanley voluntary from the standpoint of techniques to examine the availability and existing repertoire of piano instruction, but has been made to provide new and unknown works. Furthermore, the research underlying the John Stanley voluntary the piano use them in training, piano training used in the baroque repertoire the diversity of the winning students and different style and character baroque works play, students studying the piano perspectives positive effect will feel and Stanley and voluntary in Turkey ever examined that was not due to introduce the composer and his works are thought to be important. In the study of the piano works of Stanley recognition of the situation and to determine eligibility for training descriptive methods to determine the level of students to interpret these works and works against the perception of the experimental methods are used to measure. In the study, three different measurement tool is used. Stanley's work evaluation form to assess achievements in the technical and musicality applied to the teaching staff and the results were analyzed by Chi-square test. Experimental process allows students to determine their level of play prepared observation forms, and additional observers scored by the researchers were resolved by taking the arithmetic mean. Finally, the levels of difficulty in students’ perceptions before and after treatment were measured and were analyzed by Mann Whitney U test. In the study, developed and researched the effectiveness of John Stanley voluntary availability and in the process of studying the piano repertoire of teaching staff have concluded the necessity.